MODERN EPIDEMIOLOGY OF NOSOCOMIAL INFECTIONS AND RISK FACTORS WITHIN HEALTHCARE SYSTEMS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Healthcare-associated infections represent a convergence of microbial adaptation, institutional vulnerabilities, and systemic inadequacies in infection prevention. This article examines epidemiological patterns and risk determinants through surveillance data analysis and institutional assessment frameworks. Evidence indicates that nosocomial transmission reflects not isolated breaches but structural deficiencies in healthcare delivery systems, compounded by antimicrobial resistance propagation and workforce constraints that compromise adherence to evidence-based protocols.